A Journey into the Microstructure of PVDF Made by RAFT. Issue 20 (6th June 2016) - Guerre, Marc; Lopez, Gérald; Soulestin, Thibaut; Totée, Cédric; Améduri, Bruno; Silly, Gilles; Ladmiral, Vincent
Abstract : Poly(vinylidene fluoride) (PVDF) is a very important fluoropolymer. It possesses high resistances to weathering or ageing and to chemical and thermal aggressions, as well as unique electroactive properties. The reversible‐deactivation radical polymerization (RDRP) of VDF can, so far, only be achieved via degenerative transfer using ITP (iodine transfer polymerization) or RAFT (reversible addition–fragmentation chain transfer). However, due to chain defects, and transfer to solvents, the RAFT polymerization of VDF produces PVDF chains with different chain ends. This article presents the results obtained from advanced 1 H, 13 C, and 19 F NMR spectroscopy experiments using decoupling strategies, to ascertain unequivocally the microstructure of the PVDF chains synthesized using RAFT polymerization. This article provides a very detailed description of the different α‐ and ω‐chain ends of PVDF51 ‐XA and reveals an uncommon NMR heteronuclear coupling between the proton of the stereocenter of the CTA R‐group and the fluorine atoms of the CF2 moiety of the first added VDF unit. Abstract : This article presents the results obtained from advanced 1 H, 13 C, and 19 F NMR spectroscopy experiments using decoupling strategies, to ascertain unequivocally the microstructure of PVDF synthesized via RAFT polymerization. An uncommon NMR heteronuclear coupling between the proton of the stereocenter of the CTA R‐group and the fluorine atoms of the CF2 moiety of the first added VDF unit is highlighted.